WAWASAN ETNOTECHNOLOGY PREACHING DI MALUKU (Tabaos Titah dan Trash Information Tulehu) - Syarifuddin Syarifuddin (DIALEKTIKA, 2020)
ABSTRACT This research deals with the.study and ectnoteknology etnoscience preaching on indigenouspeoples in the State Tulehu Central Maluku Maluku Province. The research problem the impact of modern technology on etnoscienceand ectnoteknologypreaching. T. his study uses a qualitative method The researc.hproblem is how etnosciencecollision and preaching etnoteknology with the construction of modern technology in the Moluccas. The data collection technique using Focus Group dicussion and in-depth interviews on traditional leaders, and community. This studyfound that etnoscience and etnoteknology indigenouspreaching in Tulehu very important role to provide imagery of religious social resilience to offset garbage information produced by the mass media Etnoscience and etnoteknology preaching can prevent waste circulation of negative information thai could potentially disturb the minds of people in religious teaching. understanding, and faith Etnoscience traditions and communities in the Stale etnotechnology Tulehu Patawala Maluku Province (Calling People Family); system deployment or social construction at the family level by using language etnocommunication. Pasaware (customary homage) is usually done in the mosque for holy days of Islam. Tabaos The statutes; Taboos commandment serves as a medium for the publication of the social construction of the messages Icing was resolved in Baileo (traditional house). Through etnoscience and etnoteknology tradition to maintain, nurture, culture etno-communicationas social thepower tradition in Maluku. The higher the communication process etnoscience and etnoteknologi preaching in a society increasinglylowerproduction of waste and garbage industry thinking. Keywords: etnoscience,etnoteknologi, preaching ABSTRAK Penelitian ini berkaitan dengan studi etnoscience dan etnoteknology dakwah pada masyarakat adat di Negri Tulehu Maluku Tengah Provinsi Maluku. Masalah penelitian ini memotret imbas teknologi moderen terhadap etnoscience dan etnoteknology dakwah di Desa Tulehu. Penelitian ini menggunakan metode kualitatif. Masalah penelitian ini adalah bagaimana benturan etnoscience dan etnoteknology Dakwah dengan konstruksi teknologi moderen di Maluku. Teknik pengumpulan data menggunakan metode Focus Group Dicussion dan wawancara mendalam pada tokoh adat, dan masyarakat. Kajian ini menemukan bahwa etnoscience dan etnoteknology dakwah adat di Tulehu sangat berperan untuk memberikan citra ketahanan sosial keagamaan untuk mengimbangi sampah infonnasi yang diproduksi oleh media massa. Etnoscience dan etnoteknology dakwah dapat mencegah peredaran limbah informasi negatif yang berpotensi mengganggu alam pikiran masyarakat dalam ajaran agama, pemahaman, dan keyakinannya, Tradisi etnoscience dan etnotechnology komunitas di Negri Tufehu Provinsi Maluku Potawala (komunikasi Orang Keluarga); sistem penyebaran atau konstruksi sosial yang levelnya pada ke]uarga dengan menggunakan bahasa etnokomunikasi. Pasaware (Komunikasipenghormatan adaU biasanya dilakukan di masjid untuk hari-hari besar agama IslamTabaos Titah; Tlhaos titah ini berfungsi sebagai media konstruksi sosial untuk publikasi pesan-pesan raja yang telah diputuskan dalam Baileo (rumah adat). Melalui etnoscience dan echnoteknology tradisi untuk menjaga, merawat, budaya etnokomunikasi sebagai tradisi katahanan sosial di Maluku. Kata kunci: etnoscience, etnoteknologi, dakwah